PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA DAN NILAI PERUSAHAAN - Wiranata, Sri Roso; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to determine the influence of the proportion of independent board of commissioners, auditcommittee, managerial ownership, and institutional ownership to the corporate performance which is measuredby using the ROA and firm value is measured by using Tobins Q.The population is manufacturing companieswhich are listed in Indonesia Stock Exchange in 2013-2015 periods. Samples have been selected by usingpurposive sampling technique. The numbers of samples are 36 companies of 116 manufacturing companieswhich are listed in Indonesia Stock Exchange in 2013-2015 periods. The classic assumption test which consistsof normality test, multicolinearity test, autocorrelation test and heteroscedasticity test is conducted before thedata analysis technique. The analysis method has been done by using multiple linear regressions method.Theresult of the research shows that 1) the proportion of the board of independent commissioner gives influence tothe corporate performance (ROA) and firm value. 2) The size of audit committee does not give any influence tothe corporate performance (ROA) and firm value. 3) Managerial ownership gives influence to the corporateperformance (ROA) and firm value. 4) Institutional ownership gives influence to the corporate performance(ROA) and firm value.Keywords: Good corporate governance, corporate performance, firm value